Perancangan Museum Budaya Minahasa Dengan Pendekatan Arsitektur Dekonstruksi di Kota Tomohon - Virginia Lauriana Keles; Felly Ferol Warouw; Freike E.Kawatu (Student Scientific Creativity Journal, 2024)
Culture is a determinant of the quality and even levels of human happiness. Culture is thought, reason and customs. However, the role of culture is so important, this culture still lacks attention from the government and surrounding communities. The Minahasa cultural museum in Tomohon City is a means of storing and providing information for the community and tourists to find out more about the culture in Minahasa, as a solution. The problem is that there is no Minahasa cultural museum in Tomohon City. With a Deconstruction Architecture approach by creating buildings that contrast with abstract and complicated shapes, so that they can attract tourists but can also attract local people to visit the museum.